PELATIHAN DAN PENDAMPINGAN INTERNET MARKETING DALAM RANGKA MENINGKATKAN POTENSI EKONOMI SPR (SENTRA PETERNAKAN RAKYAT) LEMBU LESTARI KABUPATEN PACITAN - Fitria Azzahra, Noor (Universitas Merdeka Madiun, 2018)
SPR Lembu Lestari is one of 50 SPR established by the Ministry of Agriculture. Its potential of natural resources and human resources should be able to increase revenues for the community. One of the important things in economic activity is marketing that aims to introduce a wide range of business activities in order to increase revenue. Facebook Ads is one of the techniques used for internet marketing. In this activity, the business that will be promoted is Eduwisata Kampung Ternak Pacitan. Facebook Ads technique used is to use the technique Near Me, so that the promotion reaches people around the location of SPR Lembu Lestari. The result during the promotional in a week has reached 3,866 people and increased interaction with the surrounding community.Â Keywords: facebook ads, marketing, revenue